Early maltreatment and current quality of relational care predict socioemotional problems among institutionalized infants and toddlers - Baptista, J.; Silva, J. R.; Marques, S.; Martins, C.; Soares, I. (Infant Mental Health Journal, 2018)
The present study is focused on child socioemotional problems 6 months after institutionalization, by considering the putative predictive role of child maltreatment, of developmental functioning at admission and the following months, and of the quality of institutional relational care. Fifty institutionalized infants and toddlers participated in this study. Child developmental functioning (i.e., cognitive, language, and motor development) was assessed at admission to the institution (Wave 0), and 3 (Wave 1) and 6 months (Wave 2) thereafter. The quality of institutional relational care—operationalized in terms of caregivers’ sensitivity and cooperation—was measured at Wave 2. Caregivers reported on the presence of disturbed socioemotional behaviors at Wave 2. Child gestational age, birth weight, age, and stunted growth at admission to the institution served as covariates. Results revealed significant associations between socioemotional difficulties and lower levels of motor development at Waves 0 and 1, child maltreatment, and less sensitive caregiving. A logistic regression showed that child maltreatment and caregiver insensitivity were the only significant predictors of disturbed socioemotional functioning by the end of 6 months of institutionalization.